The book whisperer : awakening the inner reader in every child - Miller, Donalyn (San Francisco : Jossey-Bass, 2009)
Known for her popular blog, "The Book Whisperer," Donalyn Miller says she has yet to meet a child she couldn't turn into a reader. No matter how far behind Miller's students might be when they reach her 6th grade classroom, they end up reading an average of 40 to 50 books a year. She shares her teaching methods and includes a dynamite list of recommended "kid lit" that helps parents and teachers find the books that students really like to read.
There and back again -- Everybody is a reader -- Whisper: Student surveys -- There's a time and a place -- Reading freedom -- Whisper: Reader's notebooks -- Walking the walk -- Cutting the teacher strings -- Whisper: End-of-year evaluations -- Letting go -- Afterword / Ron D. Myers -- Appendix A: The care and feeding of a classroom library -- Appendix B: Ultimate library list -- Appendix C: Student forms.
Includes bibliographical references (p. [213]-215) and index.
Keywords: Reading (Elementary); Reading (Middle school); Children -- Books and reading; Motivation in education